The Nanotechnology (Preparation, Applications, and Cancer Treatment): Review - Hayder Abbas Sallal; Mohammed Subhi Mohammed; Ishraq Abd Ulrazzaq Kadhim (Iraqi Journal of Cancer and Medical Genetics, 2020)
The medical, engineering, and technological fields witnessed a great leap in the development and improvement of the properties of various materials to use them in the best applications and benefit from them, especially in the medical fields. Materials have evolved through the introduction and development of various production methods to improve the quality of materials, and one of these methods is the method of producing nanomaterial’s that gave a quantum leap in the properties of materials compared to ordinary materials because of their distinctive effect on (engineering, medical and technological applications). Amongthe most important applications of nanotechnology in cancer treatment, the effect of this technology has been observed to treat and reduce cancer. There are multiple ways to manufacture nanomaterials, but one of the most important methods is the Sol-Gel method, So we will address the fundamentals of this process, its most important applications because This method has proven its economic and efficient to manufacture various nanomaterials in different shapes and is considered simple compared to other methods. This review deals with methods of manufacturing nanoparticles in general and the treatment of cancer.